Pilot Evaluation of a Palliative and End-of-Life Communication Intervention for Parents of Children With a Brain Tumor. (May 2017) - Hendricks-Ferguson, Verna L.; Pradhan, Kamnesh; Shih, Chie-Schin; Gauvain, Karen M.; Kane, Javier R.; Liu, Jingxia; Haase, Joan E.
Providing timely palliative and end-of-life care (PC/EOL) information to parents of children with a serious illness is a national health care priority. The goals of this study were to determine feasibility, acceptability, and parent responses related to a PC/EOL communication intervention, titled "Communication Plan: Early through End of Life (COMPLETE)" to parents of children with a brain tumor. The study was a 2-site prospective, single-group pilot study targeting parents' stress and coping outcomes. The sample included 13 parents of 11 children (ie, 11 families). During the first 6 months postdiagnosis, we evaluated parent outcomes at 4 time points (baseline and 3 post-sessions). Our findings included significant decline in decision regret ( P = .0089); strong, significantly increased hope ( P ≤ .0001); and significantly decreased uncertainty ( P = .04). Over time, more than half of the parents (61.5%) preferred to receive information about their child's current condition and PC/EOL options. Our findings provide evidence to suggest that the COMPLETE intervention is feasible and acceptable and produces promising effects on 3 parent outcomes (ie, decision regret, hope, and uncertainty) in parents of children with a brain tumor. Further research is indicated to evaluate COMPLETE with a larger sample of parents of children with cancer and with a control group.